Challenges Facing Surrogacy Today - Kovacek Stanic, Gordana; Samardžić, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Surrogacy represents perhaps the oldest form of assisted reproduction, but at the same time the most controversial form of reproduction, on which reaching any consensus at the international level is almost impossible at the moment. In the last few years, the practice of surrogacy has encountered serious obstacles and challenges, such as the COVID-19 pandemic, but also with the war on the territory of Ukraine, where surrogacy was, until recently, extremely common. As a result of this, but also the fact that some legislations have significantly tightened their regulations, the surrogacy industry has been quickly adapting and looking for alternative ways to continue to run smoothly. That’s how the so-called reprowebs, which imply a global network of reproduction consisting of several different locations, more or less connected to each other and which require answers to numerous questions in order to protect all participants in this procedure.